Characterization of pollen grain and pollen extract from common allergenic plants in the Philippines - Hate, Krystal M.; Castor, Mary Anne R.; Cruz, Maria Katrina Diana M.; Balanag, Gregg Austine M.; Salvador, Kent Isaac; Sanchez, Nicole Angelique L.; Reyes, Roche Dana C.; Agcaoili–de Jesus, Maria Socorro; Ocampo-Cervantes, Cherie C.; Dalmacio, Leslie Michelle M. (2023)
Allergic rhinitis and asthma are prevalent in tropical countries like the Philippines. Pollen grains from anemophilous plant species may trigger these respiratory allergies. Pollen extracts from common allergenic plants are currently produced locally in the Philippines and are utilized for the diagnosis and immunotherapy of patients with respiratory allergies. Further improvement of their quality is necessary to avoid false negative or false positive diagnoses, as well as to increase the effectiveness of immunotherapy and avoid adverse reactions. This study aimed to characterize the morphology of the collected pollen grains and assess the pollen purity, protein concentration, and electrophoretic profile of the allergenic pollen extracts. Pollen identification and percent purity of the pollen collections were assessed via microscopy and hemocytometer. Lowry assay was performed to identify the total protein concentration of the pollen extracts before subjecting them to SDS-PAGE
and silver staining. The pollen samples from varying plant families have distinct features that will aid in their proper identification. Collected aggregates of pollen samples with pollen purity of <90%, like T. procumbens,A. saman,L. leucocephala, andM. indica, manifest darker colors compared to their actual color. On the other hand, the color of collected pollen samples with pollen purity ≥ 90% are commonly yellow or off-white, which is their natural color. The total protein concentration of the crude pollen extracts ranges from 2.87–9.63 mg/mL. The pollen extracts revealed protein bands at molecular weights ranging from 10–250 kD on SDS-PAGE. Proper characterization of a particular pollen may help in assessing the purity of the collected pollen. Higher pollen purity may contribute to the assurance that the positive diagnosis was due to the target pollen of a plant and not due to contaminations from other components. The result of this study may be considered for the improvement of the crude pollen allergen extract production for clinical use. It is also recommended to assess the effect of the environmental condition where the pollen was collected in terms of the actual proteins present after allergen extraction
Keywords: Pollen; Allergies